The Logical Relationship Between Determinism and Pragmatism: Implications for Creative Education (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Education, as a value-laden activity, is rooted in philosophical assumptions about human nature, knowledge, and truth. Despite considerable scholarly attention to determinism and pragmatism as independent philosophical theories, most studies tend to present determinism as a rigid system of universal causal laws, and pragmatism as an experience-based philosophy that emphasizes change and the practical utility of ideas. However, insufficient attention has been given to clarifying how these two concepts intersect or complement each other in relation to creative education.This paper, therefore, explores the logical relationship between determinism and pragmatism in order to examine how they interact in fostering creativity. To achieve this, the paper begins with an exposition of the logically necessary conditions of these concepts, demonstrating how they are interconnected in such a way that each concept relates meaningfully to the other. The methodological approach adopted is philosophical, aimed at drawing out the implications for creative education. The paper argues that the relationship between determinism and pragmatism allows for flexibility and can be understood as complementary within the framework of creative education. It further highlights that creative education flourishes and innovation emerges at the intersection of determinism and pragmatism, rather than in their separation. The study affirms that a synthesis of deterministic awareness and pragmatic orientation provides a balanced philosophical foundation for fostering creativity in education. Finally, the paper recommends that educators and curriculum designers should recognize the influence of natural laws while promoting experimental learning approaches to enhance creativity through innovation and critical thinking.